Análise da produção e purificação de biodiesel etílico de óleos de soja e canola por centrifugação - Medeiros, Janaína Fernandes (2014)
The use of fossil fuels on a large scale has substantially changed the composition of the atmosphere and the heat balance of the planet, causing global warming. The use of renewable energy to replace fossil fuels is a viable and advantageous direction because, besides being practically inexhaustible, may have a very low environmental impact. Biodiesel is one of the options to be an alternative, renewable, biodegradable and non-toxic fuel. In this study the production of biodiesel occurred by transesterification using degummed soy oil and crude canola with ethanol, in the presence of catalyst sodium hydroxide. The main advantage of using ethanol is its source, because it is a derivative of biomass, making biodiesel a truly renewable product. However, there is a difficulty in separation of phases, biodiesel and glycerol, formed after the reaction of ethyl transesterification. An alternative is the use of a centrifuge process which speeds up the process of decantation. The objective of this study was to analyze the purification of biodiesel by centrifugation, showing the viability of this process compared to the conventional process of purification of biodiesel, which consists in removing the ethanol and subsequent washing with heated and / or acidified water and decanting. In order to eliminate the stage of ethanol withdrawal, thereby reducing the energy that would be used if it continued to centrifugation without ethanol withdrawal. However, preliminary results showed that the centrifugation without removal of ethanol there was no phase separation, then was added to biodiesel different concentrations of water or acidified water (0.5, 1 and 2 %) or solution saturated sodium chloride. The efficiency of the purification of biodiesel was analyzed by the content of glycerol in the biodiesel phase (upper phase) which has a permitted limit of 0.02% for ANP. The best result centrifugation for soybean biodiesel and also for canola were achieved with a concentration of 10% water, with a rotation of 2000 rpm and a time of 5 minutes, showing the efficiency of the method for purification to biodiesel.